Analytical and Clinical Analysis of Two Automated Anti-SARS-CoV-2 Immunoassays in Pre-Pandemic and Pandemic Patient Populations. (22nd December 2020) - Yang, Jianbo; Pederson, Edward C; Hamilton, Christopher; Neibauer, Terri; Robyak, Kimberly; McGhee, Pamela; Speicher, Teresa; Zhu, Yusheng
Abstract: Background: In the absence of a safe, effective vaccine, the worldwide spread of COVID-19 (SARS-CoV-2) infection will continue. Laboratory tests with ideal precision, sensitivity, and specificity should be used in public health and clinical settings to gauge the extent of virus exposure. Toward this end, we evaluated the analytical and clinical performance of the Abbott SARS-CoV-2 IgG and the Roche Anti-SARS-CoV-2 immunoassays. Methods: Quality control, pooled COVID-19, and non-COVID-19 patient specimens were used for the imprecision study. Two hundred and forty-six specimens from 70 patients with COVID-19 diagnosis were tested to study the sensitivity. Seventy-three non-COVID-19 control specimens were measured to study the specificity. All specimens were analyzed by both assays. Results: Total analytic variability (CV) of the negative and positive controls were 5.5% and 3.6% for the Abbott assay and 4.5% and 1.9% for the Roche assay. Both assays demonstrated 100% qualitative reproducibility of negative and positive controls. The clinical specificities of the Abbott and the Roche assays were 100% (95% CI: 94%—100%) and 97% (95% CI: 90%—100%), respectively. The clinical sensitivities of the Abbott assay were 49% (95% CI: 41%—56%), 86% (95% CI: 74%—93%), and 100% (95% CI: 76%—100%) for samples collected at 0–6 days, 7–13 days, and ≥14 days after the first RT-PCR, while the sensitivities of the Roche assay were 55% (95% CI: 47%—62%), 86% (95% CI: 74%—93%), and 100% (95% CI: 76%—100%). Conclusions: This study demonstrates similar analytical and clinical performance of the Abbott and the Roche SARS-CoV-2 antibody assays, but the Roche assay may be slightly more sensitive for patients tested within 0–6 days after first positive RT-PCR of SARS-CoV-2. COVID-19 is a respiratory infectious disease caused by SARS-CoV-2. Laboratory tests with ideal precision, sensitivity, and specificity should be used in public health and clinical settings. We analyzed analytical and clinical performance of the Roche and Abbott SARS-CoV-2 antibody assays in pre-pandemic and pandemic patient populations. Additionally, we analyzed the sensitivity of both assays in patients at different stages of the disease. The 2 assays showed similar analytical and clinical performance, but the Roche assay may be slightly more sensitive for patients tested within 0–6 days after first positive RT-PCR of SARS-CoV-2. Our findings help other clinical labs select appropriate assays for SARS-CoV-2 antibody testing.